Electromagnetic wave shielding film, method for producing the same, and use thereof

CN122995118APending Publication Date: 2026-10-27ZHEJIANG DAHUA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611241595.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

传统方案主要采用宽频屏蔽材料,通过体屏蔽效应可以在全频段衰减,从而在宽频段范围抑制电磁波干扰,然而,这类材料无法屏蔽特定的频段,即无法实现屏蔽特定干扰信号和选择性透有用信号,导致设备内部信号传输效率下降或功能异常

Benefits of technology

[0061]本发明中,通过将特定电磁波屏蔽频段的高频软磁复合材料与具有特定材质及孔隙率的第一电磁屏蔽颗粒分散于第一基体中,协同作用形成可屏蔽高频段干扰信号的高频层;通过选择特定电磁波屏蔽频段的低频软磁复合材料与特定材质及孔隙率的第二电磁屏蔽颗粒分散于第二基体中,协同作用形成可屏蔽低频段干扰信号的低频层,在高频层与低频层的共同作用下,能够实现对特定频段的干扰信号屏蔽,同时不会影响该频段以外其他有用信号的正常透传,从而在保证设备功能稳定运行的同时,减少不同信号噪声之间的相互干扰,净化电子设备内部空间的电磁环境,获得优异的综合电磁波抑制效果。此外,本发明还可以利用材料本身的特性,赋予电磁波屏蔽膜较高的柔性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to an electromagnetic wave shielding film and a preparation method and application thereof, the electromagnetic wave shielding film comprising: at least one high-frequency layer and at least one low-frequency layer, which are alternately stacked; the high-frequency layer comprising a first base body, a high-frequency soft magnetic composite material with a shielding frequency band x, and first electromagnetic shielding particles; the low-frequency layer comprising a second base body, a low-frequency soft magnetic composite material with a shielding frequency band y, second electromagnetic shielding particles, 60<=x<=80GHz, 1<=y<=4GHz; the porosity of the first electromagnetic shielding particles and the second electromagnetic shielding particles is independently selected from the range of 15%-45%, the first electromagnetic shielding particles and the second electromagnetic shielding particles respectively comprising a third base body and a composite filler and conductive fibers dispersed in the third base body, the material of the third base body comprising at least graphene, and the composite filler comprising a topological insulator and a soft magnetic alloy. The electromagnetic wave shielding film of the present application can realize selective transmission of useful signals and effective shielding of interference signals, and has high flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic shielding technology, and in particular to an electromagnetic wave shielding film, its preparation method, and its application. Background Technology

[0002] Electronic devices typically contain multiple electromagnetic frequency bands. Signals from different frequency bands can interfere with each other during transmission, affecting communication quality, yet they also need to interact when necessary to achieve overall functionality. Therefore, for the modular units of electronic devices, it is essential to suppress unwanted signals while preventing the shielding of useful signals. Traditional solutions mainly employ broadband shielding materials, which can attenuate electromagnetic interference across the entire frequency band through bulk shielding effects, thus suppressing electromagnetic interference over a wide range. However, these materials cannot shield specific frequency bands, meaning they cannot achieve both shielding specific interference signals and selectively transmitting useful signals, leading to decreased signal transmission efficiency or malfunctions within the device. Summary of the Invention

[0003] Therefore, it is necessary to provide an electromagnetic wave shielding film, its preparation method, and its application to address the above problems. The electromagnetic wave shielding film can selectively transmit useful signals and effectively shield interference signals, and has high flexibility.

[0004] An electromagnetic wave shielding film, comprising: at least one high-frequency layer and at least one low-frequency layer, wherein the high-frequency layer and the low-frequency layer are alternately stacked, wherein the high-frequency layer comprises a first substrate and a high-frequency soft magnetic composite material and a first electromagnetic shielding particle dispersed in the first substrate, and the low-frequency layer comprises a second substrate and a low-frequency soft magnetic composite material and a second electromagnetic shielding particle dispersed in the second substrate;

[0005] Wherein, the electromagnetic wave shielding frequency band of the high-frequency soft magnetic composite material is x, and the electromagnetic wave shielding frequency band of the low-frequency soft magnetic composite material is y, wherein 60GHz≤x≤80GHz, 1GHz≤y≤4GHz;

[0006] The porosity of the first electromagnetic shielding particle and the second electromagnetic shielding particle is independently selected from 15% to 45%, and the first electromagnetic shielding particle and the second electromagnetic shielding particle respectively include a third matrix and a composite filler and conductive fibers dispersed in the third matrix. The material of the third matrix includes at least graphene, and the composite filler includes a topological insulator and a soft magnetic alloy.

[0007] In one embodiment, the porosity range of the first electromagnetic shielding particle is smaller than that of the second electromagnetic shielding particle.

[0008] And / or, the porosity variation rate K of the first electromagnetic shielding particle and the second electromagnetic shielding particle satisfies: 2×(n1-n2) / H≤K≤4×(n1-n2) / H, where n1 is the maximum porosity, n2 is the minimum porosity, and H is the thickness of the electromagnetic wave shielding film.

[0009] In one embodiment, at least one of the following conditions is met:

[0010] (1) The porosity of the first electromagnetic shielding particle ranges from 15% to 25%;

[0011] (2) The porosity of the second electromagnetic shielding particle ranges from 35% to 45%;

[0012] (3) The thickness of the high-frequency layer is 0.3mm~0.5mm;

[0013] (4) The thickness of the low-frequency layer is 0.5mm~0.8mm;

[0014] (5) The mass ratio of the high-frequency soft magnetic composite material, the first electromagnetic shielding particles, and the first matrix is ​​1:0.8:3~3:2.4:10;

[0015] (6) The mass ratio of the low-frequency soft magnetic composite material, the second electromagnetic shielding particles, and the second matrix is ​​2:1.5:3~3:4:6;

[0016] (7) The maximum particle size of both the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material is greater than or equal to 20 μm;

[0017] (8) The maximum particle size of both the first electromagnetic shielding particle and the second electromagnetic shielding particle is greater than or equal to 30 μm;

[0018] (9) The mass fraction of the third matrix in the first electromagnetic shielding particle is more than 50%, and the mass fraction of the composite filler in the first electromagnetic shielding particle is greater than the mass fraction of the conductive fiber in the first electromagnetic shielding particle.

[0019] (10) The mass fraction of the third matrix in the second electromagnetic shielding particle is more than 50%, and the mass fraction of the composite filler in the second electromagnetic shielding particle is greater than the mass fraction of the conductive fiber in the second electromagnetic shielding particle.

[0020] In one embodiment, at least one of the following conditions is met:

[0021] (1) The high-frequency soft magnetic composite material is selected from at least one of Ni-Zn soft magnetic alloy or its oxide, Co-Zn soft magnetic alloy or its oxide, Fe-Ni soft magnetic alloy or its oxide, and Co-Fe soft magnetic alloy or its oxide;

[0022] (2) The low-frequency soft magnetic composite material is selected from at least one of Mn-Zn soft magnetic alloy or its oxide, Cu-Zn soft magnetic alloy or its oxide;

[0023] (3) The average particle size of the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material are independently selected from 5μm to 10μm;

[0024] (4) The average particle size of the first electromagnetic shielding particle and the second electromagnetic shielding particle are independently selected from 15μm to 25μm;

[0025] (5) In the first electromagnetic shielding particle, the mass ratio of the third matrix, the composite filler and the conductive fiber is 10~15:4~6:2~4;

[0026] (6) In the second electromagnetic shielding particle, the mass ratio of the third matrix, the composite filler and the conductive fiber is 10~15:4~6:2~4.

[0027] In one embodiment, at least one of the following conditions is met:

[0028] (1) The first matrix and the second matrix are each independently selected from at least one of epoxy resin, polyurethane or silicone resin;

[0029] (2) The material of the third matrix is ​​graphene, or the material of the third matrix is ​​a metal cation crosslinked graphene-carboxylate composite material;

[0030] (3) The composite filler is a composite of a topological insulator and a soft magnetic alloy;

[0031] (4) The conductive fiber comprises carbon-based fiber and a polymer layer and a metal layer sequentially coated on the surface of the carbon-based fiber;

[0032] (5) The aspect ratio of the conductive fiber is 1:5 to 1:7.

[0033] In one embodiment, at least one of the following conditions is met:

[0034] (1) The graphene is selected from graphene oxide;

[0035] (2) The metal cation is selected from Eu 3+ ;

[0036] (3) The carboxylate is selected from sodium alginate;

[0037] (4) In the metal cation crosslinked graphene-carboxylate composite material, the mass ratio of graphene to carboxylate is 1:2~3:8, and the molar ratio of carboxylate to metal cation is 2:1~4:1;

[0038] (5) The mass ratio of topological insulator to soft magnetic alloy in the composite filler is 1:1 to 1:3;

[0039] (6) The topological insulator is selected from nano-Bi2Se3;

[0040] (7) The soft magnetic alloy is selected from at least one of FeCo alloy or FeNiCo alloy;

[0041] (8) The particle size of the composite filler is 100nm~300nm;

[0042] (9) The polymer layer is selected from polydopamine layers;

[0043] (10) The metal layer is selected from liquid metal layers;

[0044] (11) The mass ratio of carbon-based fiber, polymer layer and metal layer in the conductive fiber is 1:1:2~2:1:8.

[0045] A method for preparing an electromagnetic wave shielding film as described above includes the following steps:

[0046] First, the composite filler is magnetized. Then, the material of the third matrix, the composite filler and the conductive fiber are mixed and freeze-dried in a temperature gradient field below 0°C. Then, the mixture is ball-milled to obtain the first electromagnetic shielding particles and the second electromagnetic shielding particles, respectively.

[0047] The freeze-drying process for preparing the first electromagnetic shielding particle and the second electromagnetic shielding particle independently includes a first stage, a second stage and a third stage performed sequentially, with the temperature of the first stage being T1, the temperature of the second stage being T2, and the temperature of the third stage being T3, where T1 > T3 > T2.

[0048] The first electromagnetic shielding particles are mixed with a high-frequency soft magnetic composite material under a magnetic field strength of B1, then mixed with a first matrix, and then pressed to obtain a high-frequency layer; the second electromagnetic shielding particles are mixed with a low-frequency soft magnetic composite material under a magnetic field strength of B2, then mixed with a second matrix, and then pressed to obtain a low-frequency layer, wherein B1 < B2. The high-frequency layer and the low-frequency layer are alternately stacked and pressed to obtain an electromagnetic wave shielding film.

[0049] In one embodiment, at least one of the following conditions is met:

[0050] (1) The magnetization treatment of the composite filler is carried out in a pulsed magnetic field with a magnetic field strength of 0.3T~0.5T and a frequency of 1Hz~10Hz;

[0051] (2) The mixing of the material of the third matrix, the composite filler and the conductive fiber is carried out in an alternating magnetic field with a magnetic field strength of 10mT~20mT and a frequency of 5Hz~100Hz;

[0052] (3) The temperature T1 of the first stage is -18℃ to -22℃, and the time is 1h to 2h;

[0053] (4) The temperature T2 of the second stage is -160℃ to -180℃, and the time is 1h to 2h;

[0054] (5) The temperature T3 of the third stage is -40℃ to -60℃, and the time is 4h to 6h;

[0055] (6) The rate of temperature change from the first stage to the second stage is 10℃ / min to 30℃ / min;

[0056] (7) The rate of temperature change from the second stage to the third stage is 2℃ / min to 8℃ / min;

[0057] (8) B1 is 20mT~30mT;

[0058] (9) B2 is 40mT~50mT.

[0059] In one embodiment, when the material of the third matrix is ​​a metal cation-crosslinked graphene-carboxylate composite material, the preparation method of the metal cation-crosslinked graphene-carboxylate composite material includes: dispersing graphene into a graphene dispersion, reacting the graphene dispersion with a carboxylate and a metal salt at 40°C to 50°C for 10 to 12 hours to obtain the metal cation-crosslinked graphene-carboxylate composite material.

[0060] An application of an electromagnetic wave shielding film as described above in electronic devices.

[0061] In this invention, a high-frequency soft magnetic composite material with a specific electromagnetic wave shielding frequency band and first electromagnetic shielding particles with a specific material and porosity are dispersed in a first matrix to synergistically form a high-frequency layer capable of shielding high-frequency interference signals. Conversely, a low-frequency soft magnetic composite material with a specific electromagnetic wave shielding frequency band and second electromagnetic shielding particles with a specific material and porosity are dispersed in a second matrix to synergistically form a low-frequency layer capable of shielding low-frequency interference signals. The combined effect of the high-frequency and low-frequency layers enables shielding of interference signals in a specific frequency band without affecting the normal transmission of other useful signals outside that band. This ensures stable operation of the equipment while reducing mutual interference between different signal noises, purifying the electromagnetic environment inside the electronic device, and achieving excellent comprehensive electromagnetic wave suppression. Furthermore, this invention can utilize the inherent properties of the materials to impart high flexibility to the electromagnetic wave shielding film. Detailed Implementation

[0062] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.

[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.

[0064] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0065] This invention provides an electromagnetic wave shielding film, the electromagnetic wave shielding film comprising: at least one high-frequency layer and at least one low-frequency layer, the high-frequency layer and the low-frequency layer being alternately stacked, the high-frequency layer comprising a first substrate and a high-frequency soft magnetic composite material and a first electromagnetic shielding particle dispersed in the first substrate, the low-frequency layer comprising a second substrate and a low-frequency soft magnetic composite material and a second electromagnetic shielding particle dispersed in the second substrate;

[0066] Wherein, the electromagnetic wave shielding frequency band of the high-frequency soft magnetic composite material is x, and the electromagnetic wave shielding frequency band of the low-frequency soft magnetic composite material is y, wherein 60GHz≤x≤80GHz, 1GHz≤y≤4GHz;

[0067] The porosity of the first electromagnetic shielding particle and the second electromagnetic shielding particle is independently selected from 15% to 45%, and the first electromagnetic shielding particle and the second electromagnetic shielding particle respectively include a third matrix and a composite filler and conductive fibers dispersed in the third matrix. The material of the third matrix includes at least graphene, and the composite filler includes a topological insulator and a soft magnetic alloy.

[0068] In this invention, a high-frequency layer capable of shielding high-frequency interference signals is formed by dispersing a high-frequency soft magnetic composite material of a specific electromagnetic wave shielding frequency band with first electromagnetic shielding particles of a specific material and porosity in a first matrix. Conversely, a low-frequency layer capable of shielding low-frequency interference signals is formed by dispersing a low-frequency soft magnetic composite material of a specific electromagnetic wave shielding frequency band with second electromagnetic shielding particles of a specific material and porosity in a second matrix. Under the combined action of the high-frequency and low-frequency layers, interference signals in a specific frequency band can be shielded without affecting the normal transmission of other useful signals outside that frequency band. This ensures stable operation of the equipment while reducing mutual interference between different signal noises, purifying the electromagnetic environment inside the electronic device, and achieving excellent comprehensive electromagnetic wave suppression. Furthermore, this invention utilizes the inherent properties of the materials to endow the electromagnetic wave shielding film with high flexibility.

[0069] It should be noted that, in different application scenarios, the shielding frequency band of the electromagnetic wave shielding film of the present invention can be shifted to a specific frequency band by adjusting the composition and ratio of the material system, thereby achieving selective suppression of electromagnetic waves of different frequency bands. In particular, the electromagnetic wave shielding film of the present invention exhibits superior shielding performance in the frequency band greater than or equal to 30 GHz and less than or equal to 100 GHz.

[0070] In order to enable the electromagnetic wave shielding film to efficiently transmit useful signals, effectively shield interference signals, and have high flexibility, the mass ratio of the high-frequency soft magnetic composite material, the first electromagnetic shielding particles, and the first substrate is 1:0.8:3~3:2.4:10; the mass ratio of the low-frequency soft magnetic composite material, the second electromagnetic shielding particles, and the second substrate is 2:1.5:3~3:4:6.

[0071] To balance the performance of the electromagnetic wave shielding film in efficiently transmitting useful signals and effectively shielding interference signals, and to give it good flexibility, the thickness of the high-frequency layer is preferably 0.3mm to 0.5mm, and can be selected from 0.3mm, 0.35mm, 0.4mm, 0.45mm or 0.5mm; the thickness of the low-frequency layer is preferably 0.5mm to 0.8mm, and can be selected from 0.5mm, 0.6mm, 0.7mm or 0.8mm.

[0072] The number of high-frequency layers and low-frequency layers in the electromagnetic wave shielding film of the present invention are not limited and can be adjusted according to actual application requirements. For example, the electromagnetic wave shielding film may include a two-layer structure with one high-frequency layer and one low-frequency layer; or a three-layer structure with two high-frequency layers and one low-frequency layer sandwiched between them; or a three-layer structure with two low-frequency layers and one high-frequency layer sandwiched between them; or a four-layer structure with two low-frequency layers and two high-frequency layers, which are alternately stacked.

[0073] To effectively shield against interference signals, the first electromagnetic shielding particle and the second electromagnetic shielding particle preferably have different porosity ranges. For example, the porosity range of the first electromagnetic shielding particle is smaller than that of the second electromagnetic shielding particle. Further, the porosity range of the first electromagnetic shielding particle can be 15% to 25%, such as 15%, 17%, 20%, 22% or 25%; and the porosity range of the second electromagnetic shielding particle can be 35% to 45%, such as 35%, 37%, 40%, 42% or 45%.

[0074] In the high-frequency layer, there are first electromagnetic shielding particles with various porosities; similarly, in the low-frequency layer, there are second electromagnetic shielding particles with various porosities. Since the first or second electromagnetic shielding particles with different porosities will produce shielding effects on different frequency bands, preferably, in the high-frequency layer, the porosity of the first electromagnetic shielding particles exhibits a continuous gradient change, and the first electromagnetic shielding particles with different porosities are uniformly dispersed in the high-frequency layer; similarly, in the low-frequency layer, the porosity of the second electromagnetic shielding particles exhibits a continuous gradient change, and the second electromagnetic shielding particles with different porosities are uniformly dispersed in the low-frequency layer.

[0075] Specifically, the porosity variation rate K of the first electromagnetic shielding particle and the second electromagnetic shielding particle satisfies: 2×(n1-n2) / H≤K≤4×(n1-n2) / H, where n1 is the maximum porosity, n2 is the minimum porosity, and H is the thickness of the electromagnetic wave shielding film in mm. That is, in the high-frequency layer, the porosity of the first electromagnetic shielding particle changes continuously with the trend of K value, and in the low-frequency layer, the porosity of the second electromagnetic shielding particle changes continuously with the trend of K value.

[0076] For example, when the thickness of the electromagnetic wave shielding film is 1 mm and the porosity of the first electromagnetic shielding particles ranges from 15% to 25%, with 20% ≤ K value ≤ 40%, in the high-frequency layer, the porosity of the first electromagnetic shielding particles will increase from 15% to 25% at any value within the range of 20% to 40%. In this case, the porosity of the first electromagnetic shielding particles could include 15%, 19.5%, or 25%. Alternatively, when the thickness of the electromagnetic wave shielding film is 1.3 mm and the porosity of the second electromagnetic shielding particles ranges from 35% to 45%, with 15% ≤ K value ≤ 30.8%, in the low-frequency layer, the porosity of the second electromagnetic shielding particles will increase from 35% to 45% at any value within the range of 15% to 30.8%. In this case, the porosity of the second electromagnetic shielding particles could include 35%, 42.5%, or 51.75%. With such control, the electromagnetic wave shielding film can achieve a good selective shielding effect.

[0077] To enable the high-frequency layer to more effectively shield external interference signals, the high-frequency soft magnetic composite material is selected from at least one of Ni-Zn soft magnetic alloy or its oxide, Co-Zn soft magnetic alloy or its oxide, Fe-Ni soft magnetic alloy or its oxide, and Co-Fe soft magnetic alloy or its oxide; the low-frequency soft magnetic composite material is selected from at least one of Mn-Zn soft magnetic alloy or its oxide, and Cu-Zn soft magnetic alloy or its oxide.

[0078] In order to enable the high-frequency soft magnetic composite material or the low-frequency soft magnetic composite material to form an electromagnetic loss network more effectively in the first matrix or the second matrix, the maximum particle size of the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material is greater than or equal to 20 μm, and the average particle size of the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material is independently selected from 5 μm to 10 μm.

[0079] In order to form a multi-scale electromagnetic wave absorption structure inside the first electromagnetic shielding particle and the second electromagnetic shielding particle, the maximum particle size of the first electromagnetic shielding particle and the second electromagnetic shielding particle is greater than or equal to 30 μm, and the average particle size of the first electromagnetic shielding particle and the second electromagnetic shielding particle are independently selected from 15 μm to 25 μm.

[0080] In order to more effectively load and fix the composite material and provide sufficient mechanical support and adhesion, the first matrix and the second matrix are each independently selected from at least one of epoxy resin, polyurethane or silicone resin.

[0081] To ensure the electromagnetic wave shielding film effectively transmits useful signals while shielding interference signals, the third matrix constitutes more than 50% of the mass of the first electromagnetic shielding particles, and the composite filler constitutes a greater mass of the first electromagnetic shielding particles than the conductive fiber. Optionally, in the first electromagnetic shielding particles, the mass ratio of the third matrix, composite filler, and conductive fiber is 10~15:4~6:2~4. Similarly, in the second electromagnetic shielding particles, the third matrix constitutes more than 50% of the mass of the second electromagnetic shielding particles, and the composite filler constitutes a greater mass of the second electromagnetic shielding particles than the conductive fiber. Optionally, in the second electromagnetic shielding particles, the mass ratio of the third matrix, composite filler, and conductive fiber is 10~15:4~6:2~4.

[0082] Optionally, the material of the third matrix can be graphene only. In this case, the third matrix is ​​a graphene third matrix. In other embodiments, the material of the third matrix can be a graphene-carboxylate composite material cross-linked with metal cations. In this way, the selective transmission of useful signals and shielding of interference signals of the electromagnetic wave shielding film can be further improved.

[0083] Optionally, in the metal cation crosslinked graphene-carboxylate composite material, the metal cation can be selected from, for example, Ca... 2+ Eu 3+ Isovalent cations, preferably Eu in this invention. 3+ The carboxylate can be selected from sodium alginate, sodium polyacrylate, etc., and sodium alginate is preferred in this invention, which can improve the performance of selectively transmitting useful signals and shielding interference signals.

[0084] To further improve the performance of selectively transmitting useful signals and shielding interference signals, the mass ratio of graphene to carboxylate in the metal cation crosslinked graphene-carboxylate composite material is 1:2 to 3:8, and the molar ratio of carboxylate to metal salt is 2:1 to 4:1.

[0085] Optionally, the graphene is selected from graphene oxide, which can make the overall structure of the first electromagnetic shielding particle and the second electromagnetic shielding particle more stable.

[0086] The topological insulator and soft magnetic alloy in the composite filler can be filled and dispersed in the first electromagnetic shielding particle and the second electromagnetic shielding particle respectively, or they can be combined to form a composite and dispersed in the first electromagnetic shielding particle and the second electromagnetic shielding particle. Preferably, the composite filler is a composite of topological insulator and soft magnetic alloy, which can better improve the ability of the first electromagnetic shielding particle and the second electromagnetic shielding particle to shield interference signals in a specific frequency band.

[0087] Optionally, the mass ratio of topological insulator to soft magnetic alloy in the composite filler is preferably 1:1 to 1:3. The topological insulator is selected from BiSb, Bi2Se3, Sb2Te3, Bi2Te3, etc. In this invention, nano-Bi2Se3 is preferred, which can better synergize with the soft magnetic alloy to improve the ability to shield interference signals in specific frequency bands. The soft magnetic alloy is selected from at least one of FeCo alloy or FeNiCo alloy, which can better achieve synergy and complementarity between magnetic loss and dielectric loss, broaden the effective absorption frequency band, and may enhance the overall loss capability through interface effect.

[0088] To further improve selective shielding performance, the particle size of the composite filler is preferably 100nm~300nm.

[0089] Optionally, the conductive fiber includes carbon-based fiber and a polymer layer and a metal layer sequentially coated on the surface of the carbon-based fiber.

[0090] The carbon-based fiber can be a carbon-based fiber formed by carbonizing graphite or other materials. The carbon-based fiber has strong surface chemical inertness and few functional groups, making it difficult to effectively bond with the metal layer. Therefore, a polymer layer with strong adhesion and abundant functional groups is first coated on the surface of the carbon-based fiber. The polymer layer can be selected from at least one of polydopamine, polyethyleneimine, and polyacrylamide. The present invention prefers polydopamine layer with better adhesion.

[0091] The present invention does not limit the selection of the metal layer. Considering that liquid metal not only has high electrical and thermal conductivity, but also has the fluidity of liquid, on the one hand, it can better form a metal layer on carbon-based fibers, and on the other hand, it can adjust the connection state of the conductive network when the temperature changes, realize the adaptive reconstruction of the conductive path, optimize the selective shielding performance, and further improve the stability of the shielding performance of the first electromagnetic shielding particle and the second electromagnetic shielding particle at different temperatures. Therefore, the metal layer is preferably a liquid metal layer, such as gallium indium tin layer, gallium indium layer, gallium bismuth layer, etc., and more preferably a gallium indium tin layer.

[0092] To further improve selective shielding performance, the mass ratio of carbon-based fiber, polymer layer and metal layer in the conductive fiber is 1:1:2 to 2:1:8, and the aspect ratio of the conductive fiber is preferably 1:5 to 1:7.

[0093] To increase the reflection of electromagnetic waves on the surface of the electromagnetic wave shielding film and improve its shielding capability, the two sides of the electromagnetic wave shielding film can be roughened to obtain an electromagnetic wave shielding film with roughness.

[0094] To improve the heat dissipation capacity of the electromagnetic wave shielding film, a heat dissipation layer can be sandwiched between the high-frequency layer and the low-frequency layer. The thickness of the heat dissipation layer is preferably 0.20mm to 0.30mm. Within this thickness range, the adverse effects of the heat dissipation layer on the selective shielding performance of electromagnetic waves can be reduced.

[0095] To improve the corrosion and oxidation resistance of electromagnetic wave shielding films, an insulating layer with a thickness of approximately 0.1 mm can be applied to both sides of the shielding film. Additionally, an adhesive backing layer and a release film can be added sequentially to the outside of the insulating layer. The shielding frequency band of the electromagnetic wave shielding film can be marked on the release film. During use, the release film can be removed, and the electromagnetic wave shielding film can be fixed to the internal surface of the electronic device to be shielded via the adhesive backing layer.

[0096] In practical applications, the application position and orientation of the electromagnetic wave shielding film can be set according to specific usage requirements. For example, when the electromagnetic wave shielding film needs to function for the 77GHz frequency band, the adhesive layer can be placed on the side closer to the high-frequency layer, and the high-frequency layer can be applied with the high-frequency layer facing inwards. This can suppress the interference of the external 77GHz frequency band to the inside of the device and suppress the radiation loss of the 77GHz frequency band inside the device.

[0097] The present invention also provides a method for preparing the electromagnetic wave shielding film, comprising the following steps:

[0098] First, the composite filler is magnetized. Then, the material of the third matrix, the composite filler and the conductive fiber are mixed and freeze-dried in a temperature gradient field below 0°C. Then, the mixture is ball-milled to obtain the first electromagnetic shielding particles and the second electromagnetic shielding particles.

[0099] The freeze-drying process for preparing the first electromagnetic shielding particle and the second electromagnetic shielding particle independently includes a first stage, a second stage and a third stage performed sequentially, with the temperature of the first stage being T1, the temperature of the second stage being T2, and the temperature of the third stage being T3, where T1 > T3 > T2.

[0100] The first electromagnetic shielding particles are mixed with a high-frequency soft magnetic composite material under a magnetic field strength of B1, then mixed with a first matrix, and then pressed to obtain a high-frequency layer; the second electromagnetic shielding particles are mixed with a low-frequency soft magnetic composite material under a magnetic field strength of B2, then mixed with a second matrix, and then pressed to obtain a low-frequency layer, wherein B1 < B2. The high-frequency layer and the low-frequency layer are alternately stacked and pressed to obtain an electromagnetic wave shielding film.

[0101] Optionally, the temperature T1 of the first stage is -18℃ to -22℃, and the time of the first stage is 1h to 2h; the temperature T2 of the second stage is -160℃ to -180℃, and the time of the second stage is maintained for 1h to 2h; the temperature T3 of the third stage is -40℃ to -60℃, and the time of the third stage is 4h to 6h; thus, the porosity of the composite material can be effectively controlled.

[0102] Optionally, the temperature change rate from the first stage to the second stage is 10℃ / min to 30℃ / min; and the temperature change rate from the second stage to the third stage is 2℃ / min to 8℃ / min, thereby improving the structural stability of the composite material.

[0103] Among them, composite fillers can be made by ball milling and other methods, such as ball milling, with a rotation speed of 300 rpm to 500 rpm and a time of 1.5 h to 2 h.

[0104] Optionally, the magnetization treatment of the composite filler is carried out in a pulsed magnetic field with a magnetic field strength of 0.3T~0.5T and a frequency of 1Hz~10Hz; the mixing of the third matrix material, the composite filler and the conductive fiber is carried out in an alternating magnetic field with a magnetic field strength of 10mT~20mT and a frequency of 5Hz~100Hz, so that the components can be evenly and orderly dispersed to achieve a better shielding effect.

[0105] When the material of the third matrix is ​​a metal cation-crosslinked graphene-carboxylate composite material, the preparation method of the metal cation-crosslinked graphene-carboxylate composite material includes: dispersing graphene into a graphene dispersion, reacting the graphene dispersion with carboxylate and metal salt at 40℃~50℃ for 10h~12h to obtain the metal cation-crosslinked graphene-carboxylate composite material.

[0106] Optionally, in the step of reacting the graphene dispersion with the carboxylate and the metal salt, the mass ratio of graphene to carboxylate is 1:2 to 3:8, the molar ratio of carboxylate to metal salt is 2:1 to 4:1, and the metal salt is added in batches by dropping or other methods. When the metal salt is selected from Eu salt, EuCl3 is preferred.

[0107] Optionally, when the material of the third matrix is ​​a metal cation-crosslinked graphene-carboxylate composite material, the metal cation-crosslinked graphene-carboxylate composite material is subjected to vacuum degassing treatment before being mixed with the composite filler and conductive fiber.

[0108] When the conductive fiber includes carbon-based fiber and a polymer layer and a metal layer sequentially coated on the surface of the carbon-based fiber, the preparation method includes: first coating the surface of the carbon-based fiber with a polymer layer, and then coating the surface of the polymer layer with a metal layer.

[0109] For example, when the polymer layer is selected as a polydopamine layer, the carbon-based fibers are first placed in an alkaline solution such as sodium hydroxide, and then dopamine hydrochloride is added for polymerization; when the metal layer is selected as liquid metal, the liquid metal is first placed in an organic solvent and ultrasonically broken down to a particle size of less than or equal to 10 μm to prepare a dispersion. Then, the carbon-based fibers coated with the polymer layer are placed in the dispersion, and surface wetting is achieved by stirring and other methods. Then, the organic solvent is removed by vacuum drying and other methods to obtain conductive fibers.

[0110] Optionally, in order to optimize the shielding performance of electromagnetic waves of different frequency bands, a magnetic field is used to guide the soft magnetic composite material and the magnetized composite filler in a directional manner, thereby constructing magnetic loss networks with different densities and orientation characteristics in the high-frequency layer and the low-frequency layer respectively. The magnetic field strength B1 when the first electromagnetic shielding particle is mixed with the high-frequency soft magnetic composite material is 20mT~30mT, and the magnetic field strength B2 when the second electromagnetic shielding particle is mixed with the low-frequency soft magnetic composite material is 40mT~50mT.

[0111] Optionally, both the addition of the first matrix and the addition of the second matrix are carried out in an inert atmosphere, with a mixing temperature of 50℃~60℃ and a mixing speed of 200rpm / min~400rpm / min. The inert atmosphere can be selected from nitrogen or argon, which can ensure that the matrix material is fully dispersed between the electromagnetic shielding particles and the soft magnetic composite material, while avoiding the adverse effects of an atmosphere containing water or oxygen.

[0112] To ensure a more effective combination of the high-frequency and low-frequency layers, the pressure during the alternating lamination of the high-frequency and low-frequency layers is controlled between 2 MPa and 5 MPa.

[0113] The present invention also provides an application of the electromagnetic wave shielding film described above in electronic devices.

[0114] The technical solution of the present invention will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used without specified manufacturers are all commercially available conventional products.

[0115] Example 1

[0116] 2g of graphene oxide was dispersed in 100mL of deionized water and sonicated at 800W for 4h to obtain a graphene oxide dispersion. Then, 5g of sodium alginate was added while maintaining the temperature at 23℃, and the mixture was magnetically stirred at 60℃ for 6h until completely dissolved. Next, 0.1mol / L EuCl3 solution was added dropwise at a rate of 0.5mL / min, maintaining the pH at 5.5. 3+ The reaction was carried out in a water bath at 45°C for 12 hours with a COOH molar ratio of 1:3 to obtain Eu. 3+ Cross-linked graphene-sodium alginate composite material.

[0117] Bi2Se3 nanosheet powder and FeNiCo alloy were dynamically oriented in a pulsed magnetic field of 0.3T at a mass ratio of 1:2. The pulse frequency was 5Hz and the treatment time was 30min to obtain a composite filler composed of Bi2Se3 nanosheets and FeNiCo alloy. The average particle size of the composite filler was 150nm.

[0118] Carbon-based fibers obtained by carbonizing graphite at 2000℃ were immersed in a NaOH buffer solution with a pH of 8.5. Then, 2 mg / mL of dopamine hydrochloride was added at a carbon-based fiber to dopamine mass ratio of 3:2. The mixture was vibrated and polymerized at 25℃ for 24 h, resulting in a polydopamine layer with a thickness of 20 nm on the carbon-based surface. Next, GaInSn alloy with a particle size of 10 μm was ultrasonically broken up in ethanol for 30 min to obtain a mixture. The polydopamine-coated carbon-based fibers were then placed in the mixture at a GaInSn alloy to carbon-based fiber mass ratio of 3:1. Surface wetting was achieved by mechanical stirring at 2000 rpm. Ethanol was removed by vacuum drying at 60℃ to obtain conductive fibers with an aspect ratio of 1:6.

[0119] Eu 3+ The cross-linked graphene-sodium alginate composite material was subjected to vacuum degassing at 0.01 MPa. Then, it was mixed with composite filler and conductive fiber at a mass ratio of 12:5:3 in an alternating magnetic field with a magnetic field strength of 15 mT and a frequency of 50 Hz. The mixture was then freeze-dried. The freeze-drying process involved freezing at -20℃ for 2 h, followed by rapid cooling to -170℃ with liquid nitrogen at a rate of -5℃ / min and holding for 1.5 h. Then, the temperature was increased to -50℃ at a rate of 6℃ / min and held for 5 h. Finally, the mixture was ball-milled to obtain first electromagnetic shielding particles and second electromagnetic shielding particles. The particle size of both the first and second electromagnetic shielding particles was 20 μm, the porosity range was 20%~40%, and the porosity variation rate K was 15%~30%.

[0120] Ni-Zn soft magnetic alloy with a particle size of 8 μm and first electromagnetic shielding particles were mixed under an alternating magnetic field of 25 mT at a stirring rate of 200 rpm / min. Then, epoxy resin was added, and the mixture was stirred at 300 rpm / min under a nitrogen atmosphere and at 55°C. The mass ratio of the first electromagnetic shielding particles, Ni-Zn soft magnetic alloy, and epoxy resin was 2.4:2:10. The mixture was then pressed to obtain a high-frequency layer with a thickness of 0.4 mm. Mn-Zn soft magnetic alloy with a particle size of 8 μm was then used. The alloy and the second electromagnetic shielding particles were mixed under an alternating magnetic field of 50 mT at a stirring rate of 200 rpm / min. Then, epoxy resin was added and mixed under a nitrogen atmosphere at 55°C at a stirring rate of 300 rpm / min. The mass ratio of the second electromagnetic shielding particles, Mn-Zn soft magnetic alloy and epoxy resin was 4:3:6. The mixture was then pressed to obtain a low-frequency layer with a thickness of 0.7 mm. A high-frequency layer and a low-frequency layer were then stacked and pressed at 3.5 MPa to obtain an electromagnetic wave shielding film.

[0121] Example 2

[0122] The difference between Example 2 and Example 1 is only that: when preparing the first electromagnetic shielding particle, the temperature of the third stage is -40℃, resulting in a first electromagnetic shielding particle with a particle size of 18μm, a porosity range of 15%~25%, and a porosity change rate K of 20%~40%; when preparing the second electromagnetic shielding particle, the temperature of the third stage is -60℃, resulting in a second electromagnetic shielding particle with a particle size of 22μm, a porosity range of 35%~45%, and a porosity change rate K of 15%~30.8%.

[0123] Example 3

[0124] The only difference between Example 3 and Example 2 is that the Ni-Zn soft magnetic alloy in the high-frequency layer is replaced with the Mn-Zn soft magnetic alloy, and the Mn-Zn soft magnetic alloy in the low-frequency layer is replaced with the Ni-Zn soft magnetic alloy.

[0125] Example 4

[0126] The only difference between Example 4 and Example 1 is that in the high-frequency layer, the mass ratio of Ni-Zn soft magnetic alloy, the first electromagnetic shielding particles and epoxy resin is 1:0.8:3; in the low-frequency layer, the mass ratio of Mn-Zn soft magnetic alloy, the second electromagnetic shielding particles and epoxy resin is 2:1.5:3.

[0127] Example 5

[0128] The only difference between Example 5 and Example 1 is that the Ni-Zn soft magnetic alloy is replaced with Fe-Ni, and the Mn-Zn soft magnetic alloy is replaced with Cu-Zn.

[0129] Example 6

[0130] The only difference between Example 6 and Example 1 is that two high-frequency layers and two low-frequency layers are alternately stacked and pressed together at 4.0 MPa to obtain an electromagnetic wave shielding film.

[0131] Comparative Example 1

[0132] The only difference between Comparative Example 1 and Example 1 is that during the freeze-drying process, the particles were first frozen at -20°C for 2 hours, then rapidly cooled to -50°C at a rate of 10°C / min and maintained for 5 hours, then rapidly cooled to -170°C at a rate of 30°C / min and maintained for 1.5 hours, and then ball-milled to obtain the first electromagnetic shielding particles and the second electromagnetic shielding particles with a porosity range of 5% to 15%.

[0133] Comparative Example 2

[0134] The only difference between Comparative Example 2 and Example 1 is that conductive fibers are not added, resulting in first electromagnetic shielding particles and second electromagnetic shielding particles with a porosity range of 5% to 20%.

[0135] Comparative Example 3

[0136] The only difference between Comparative Example 3 and Example 2 is that the Mn-Zn soft magnetic alloy in the low-frequency layer is replaced with a Ni-Zn soft magnetic alloy.

[0137] Comparative Example 4

[0138] The only difference between Comparative Example 4 and Example 2 is that the Ni-Zn soft magnetic alloy in the high-frequency layer is replaced with Mn-Zn soft magnetic alloy.

[0139] The shielding performance of the electromagnetic wave shielding films obtained in the above embodiments and comparative examples was tested, and the results are shown in Table 1.

[0140] Table 1

[0141]

[0142] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. An electromagnetic wave shielding film, characterized in that, The electromagnetic wave shielding film includes at least one high-frequency layer and at least one low-frequency layer, wherein the high-frequency layer and the low-frequency layer are alternately stacked, the high-frequency layer includes a first substrate and a high-frequency soft magnetic composite material and a first electromagnetic shielding particle dispersed in the first substrate, and the low-frequency layer includes a second substrate and a low-frequency soft magnetic composite material and a second electromagnetic shielding particle dispersed in the second substrate. Wherein, the electromagnetic wave shielding frequency band of the high-frequency soft magnetic composite material is x, and the electromagnetic wave shielding frequency band of the low-frequency soft magnetic composite material is y, wherein 60GHz≤x≤80GHz, 1GHz≤y≤4GHz; The porosity of the first electromagnetic shielding particle and the second electromagnetic shielding particle is independently selected from 15% to 45%, and the first electromagnetic shielding particle and the second electromagnetic shielding particle respectively include a third matrix and a composite filler and conductive fibers dispersed in the third matrix. The material of the third matrix includes at least graphene, and the composite filler includes a topological insulator and a soft magnetic alloy.

2. The electromagnetic wave shielding film according to claim 1, characterized in that, The porosity range of the first electromagnetic shielding particle is smaller than that of the second electromagnetic shielding particle. And / or, the porosity variation rate K of the first electromagnetic shielding particle and the second electromagnetic shielding particle satisfies: 2×(n1-n2) / H≤K≤4×(n1-n2) / H, where n1 is the maximum porosity, n2 is the minimum porosity, and H is the thickness of the electromagnetic wave shielding film.

3. The electromagnetic wave shielding film according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: (1) The porosity of the first electromagnetic shielding particle ranges from 15% to 25%; (2) The porosity of the second electromagnetic shielding particle ranges from 35% to 45%; (3) The thickness of the high-frequency layer is 0.3mm~0.5mm; (4) The thickness of the low-frequency layer is 0.5mm~0.8mm; (5) The mass ratio of the high-frequency soft magnetic composite material, the first electromagnetic shielding particles, and the first matrix is ​​1:0.8:3~3:2.4:10; (6) The mass ratio of the low-frequency soft magnetic composite material, the second electromagnetic shielding particles, and the second matrix is ​​2:1.5:3~3:4:6; (7) The maximum particle size of both the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material is greater than or equal to 20 μm; (8) The maximum particle size of both the first electromagnetic shielding particle and the second electromagnetic shielding particle is greater than or equal to 30 μm; (9) The mass fraction of the third matrix in the first electromagnetic shielding particle is more than 50%, and the mass fraction of the composite filler in the first electromagnetic shielding particle is greater than the mass fraction of the conductive fiber in the first electromagnetic shielding particle. (10) The mass fraction of the third matrix in the second electromagnetic shielding particle is more than 50%, and the mass fraction of the composite filler in the second electromagnetic shielding particle is greater than the mass fraction of the conductive fiber in the second electromagnetic shielding particle.

4. The electromagnetic wave shielding film according to claim 3, characterized in that, At least one of the following conditions must be met: (1) The high-frequency soft magnetic composite material is selected from at least one of Ni-Zn soft magnetic alloy or its oxide, Co-Zn soft magnetic alloy or its oxide, Fe-Ni soft magnetic alloy or its oxide, and Co-Fe soft magnetic alloy or its oxide; (2) The low-frequency soft magnetic composite material is selected from at least one of Mn-Zn soft magnetic alloy or its oxide, Cu-Zn soft magnetic alloy or its oxide; (3) The average particle size of the high-frequency soft magnetic composite material and the low-frequency soft magnetic composite material are independently selected from 5μm to 10μm; (4) The average particle size of the first electromagnetic shielding particle and the second electromagnetic shielding particle are independently selected from 15μm to 25μm; (5) In the first electromagnetic shielding particle, the mass ratio of the third matrix, the composite filler and the conductive fiber is 10~15:4~6:2~4; (6) In the second electromagnetic shielding particle, the mass ratio of the third matrix, the composite filler and the conductive fiber is 10~15:4~6:2~4.

5. The electromagnetic wave shielding film according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: (1) The first matrix and the second matrix are each independently selected from at least one of epoxy resin, polyurethane or silicone resin; (2) The material of the third matrix is ​​graphene, or the material of the third matrix is ​​a metal cation crosslinked graphene-carboxylate composite material; (3) The composite filler is a composite of a topological insulator and a soft magnetic alloy; (4) The conductive fiber comprises carbon-based fiber and a polymer layer and a metal layer sequentially coated on the surface of the carbon-based fiber; (5) The aspect ratio of the conductive fiber is 1:5 to 1:

7.

6. The electromagnetic wave shielding film according to claim 5, characterized in that, At least one of the following conditions must be met: (1) The graphene is selected from graphene oxide; (2) The metal cation is selected from Eu 3+ ; (3) The carboxylate is selected from sodium alginate; (4) In the metal cation crosslinked graphene-carboxylate composite material, the mass ratio of graphene to carboxylate is 1:2~3:8, and the molar ratio of carboxylate to metal cation is 2:1~4:1; (5) The mass ratio of topological insulator to soft magnetic alloy in the composite filler is 1:1 to 1:3; (6) The topological insulator is selected from nano-Bi2Se3; (7) The soft magnetic alloy is selected from at least one of FeCo alloy or FeNiCo alloy; (8) The particle size of the composite filler is 100nm~300nm; (9) The polymer layer is selected from polydopamine layers; (10) The metal layer is selected from liquid metal layers; (11) The mass ratio of carbon-based fiber, polymer layer and metal layer in the conductive fiber is 1:1:2~2:1:

8.

7. A method for preparing an electromagnetic wave shielding film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: First, the composite filler is magnetized. Then, the material of the third matrix, the composite filler and the conductive fiber are mixed and freeze-dried in a temperature gradient field below 0°C. Then, the mixture is ball-milled to obtain the first electromagnetic shielding particles and the second electromagnetic shielding particles, respectively. The freeze-drying process for preparing the first electromagnetic shielding particle and the second electromagnetic shielding particle independently includes a first stage, a second stage and a third stage performed sequentially, with the temperature of the first stage being T1, the temperature of the second stage being T2, and the temperature of the third stage being T3, where T1 > T3 > T2. The first electromagnetic shielding particles are mixed with a high-frequency soft magnetic composite material under a magnetic field strength of B1, then mixed with a first matrix, and then pressed to obtain a high-frequency layer; the second electromagnetic shielding particles are mixed with a low-frequency soft magnetic composite material under a magnetic field strength of B2, then mixed with a second matrix, and then pressed to obtain a low-frequency layer, wherein B1 < B2. The high-frequency layer and the low-frequency layer are alternately stacked and pressed to obtain an electromagnetic wave shielding film.

8. The method for preparing the electromagnetic wave shielding film according to claim 7, characterized in that, At least one of the following conditions must be met: (1) The magnetization treatment of the composite filler is carried out in a pulsed magnetic field with a magnetic field strength of 0.3T~0.5T and a frequency of 1Hz~10Hz; (2) The mixing of the material of the third matrix, the composite filler and the conductive fiber is carried out in an alternating magnetic field with a magnetic field strength of 10mT~20mT and a frequency of 5Hz~100Hz; (3) The temperature T1 of the first stage is -18℃ to -22℃, and the time is 1h to 2h; (4) The temperature T2 of the second stage is -160℃ to -180℃, and the time is 1h to 2h; (5) The temperature T3 of the third stage is -40℃ to -60℃, and the time is 4h to 6h; (6) The rate of temperature change from the first stage to the second stage is 10℃ / min to 30℃ / min; (7) The rate of temperature change from the second stage to the third stage is 2℃ / min to 8℃ / min; (8) B1 is 20mT~30mT; (9) B2 is 40mT~50mT.

9. The method for preparing the electromagnetic wave shielding film according to claim 7, characterized in that, When the material of the third matrix is ​​a metal cation-crosslinked graphene-carboxylate composite material, the preparation method of the metal cation-crosslinked graphene-carboxylate composite material includes: dispersing graphene into a graphene dispersion, reacting the graphene dispersion with carboxylate and metal salt at 40℃~50℃ for 10h~12h to obtain the metal cation-crosslinked graphene-carboxylate composite material.

10. The application of an electromagnetic wave shielding film as described in any one of claims 1 to 6 in an electronic device.